Admission test cardiotocography in labour as a predictor of foetal outcome in high risk pregnancies - Kumar, Anvesha; Jaju, Purshottam Bantaklal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Continuous fetal heart monitoring in all pregnant women in labour has gained prominence in obstetric practice in the recent years. The aim of this study was to emphasize on the role of admission cardiotocography (CTG) in labour as a predictor of foetal outcome in high risk pregnancies. Methods: This was a prospective observational study done on 340 high risk patients admitted in labour with a period of gestation of ≥37 weeks. An admission CTG which consists of a 20-minute recording of FHR and uterine contractions was taken and the foetal outcome was correlated with it. The non-parametric Chi-square test was used for statistical calculations and a p valve of <0.05 was considered to designate statistical significance. Results: The admission CTG was reactive in 69.4% of all patients, equivocal in 22.2% and pathological in 8.4% of the 340 recruited patients. A total of 37.5% of the patients were post-dated followed by 20.6% of pregnancy incuded hypertensive patients. The neonatal outcomes in terms of fetal distress, meconium stained liquor, NICU admission were considerably higher in pathological test. The specificity of the test was 53.3%, and the negative predictive was 86.49%. Conclusions: Admission CTG is a simple, useful screening test and serves as a non-invasive tool in forecasting the adverse foetal outcomes in high risk pregnancies.